2014
DOI: 10.1002/psp.1871
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Service and Infrastructure Provision on Indigenous Temporary Mobility in the Northern Territory of Australia: Insights from the 2011 Census

Abstract: Indigenous people comprise a significant proportion of the population living in remote parts of Australia, particularly in the north. A growing body of literature has documented high mobility between remote Indigenous settlements, service towns and cities. The extent and nature of this mobility is thought to be driven, at least partly, by the types of services and infrastructure available in communities. Understanding to what extent these service and infrastructure provisions drive people's mobility and the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
(79 reference statements)
0
0
0
Order By: Relevance
“…Service coordination and effective referral links in PHC are crucial if a patient is to receive continued quality care. In our study, although health service acceptability (86%-97%) [44,65,75], and service use [63,64,68,70,89,103,104,125] (Table S7 in the Online Supplementary Document) have increased over time, the number of referrals for behavioural risks for chronic diseases was not increased [129]. Similarly, a study reported that only 38%-49% of chronic disease patients received a referral for their complex health care needs including mental health [53].…”
Section: Person / Patient-centerednessmentioning
confidence: 49%
See 2 more Smart Citations
“…Service coordination and effective referral links in PHC are crucial if a patient is to receive continued quality care. In our study, although health service acceptability (86%-97%) [44,65,75], and service use [63,64,68,70,89,103,104,125] (Table S7 in the Online Supplementary Document) have increased over time, the number of referrals for behavioural risks for chronic diseases was not increased [129]. Similarly, a study reported that only 38%-49% of chronic disease patients received a referral for their complex health care needs including mental health [53].…”
Section: Person / Patient-centerednessmentioning
confidence: 49%
“…The overall characteristics of included studies are summarized in each section of the key attributes of good PHC delivery [19]. Of 112 studies included, methodologically, 29 were qualitative studies [17,, 20 were cross-sectional [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], 15 were mixed-method studies [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86], 10 were national / state based surveys / census [87][88][89][90][91][92][93][94][95][96], nine were retrospective / prospective cohort [97][98]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation